2021
DOI: 10.1177/21582440211040118
|View full text |Cite
|
Sign up to set email alerts
|

Linking Proactive Personality to Well-Being: The Mediating Role of Person-Environment Fit

Abstract: This study used work adjustment theory to develop a model of linking proactive personality to employee job satisfaction, career satisfaction, and job involvement. This model was tested using two samples. The first sample, collected using a cross-sectional survey, consisted of 278 employees nested in 25 organizations located in Taiwan, including 17 service organizations and eight manufacturing organizations. The second sample, collected using a two-wave survey, consisted of 300 employees nested in 22 organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 98 publications
(187 reference statements)
1
8
0
2
Order By: Relevance
“…Boon et al . (2011), Mostafa and Gould-Williams (2014) and Liao (2021) also supported the influence of person-organization fit on job satisfaction, which can be associated with workplace well-being. The results of this study is in line with the above mentioned authors, since it was proven that person-organization fit has a positive effect on workplace well-being .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Boon et al . (2011), Mostafa and Gould-Williams (2014) and Liao (2021) also supported the influence of person-organization fit on job satisfaction, which can be associated with workplace well-being. The results of this study is in line with the above mentioned authors, since it was proven that person-organization fit has a positive effect on workplace well-being .…”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, researchers like Boon et al . (2011), Mostafa and Gould-Williams (2014) and Liao (2021) have also supported the influence of person-organization fit on job satisfaction, which is associated with workplace well-being. Takeuchi and Takeuchi (2013) underscored the importance of exploring the psychological needs of employees in their study.…”
Section: Theory and Hypothesesmentioning
confidence: 82%
See 1 more Smart Citation
“…Proactive personality literature has shown that proactive personality is positively associated with job satisfaction (e.g., Liao, 2015Liao, , 2021 and career satisfaction (e.g., Jawahar & Liu, 2017). There is a limited number of studies that have explored the role of proactive personality in the academic context and the relationship between proactive personality and academic satisfaction.…”
Section: Proactive Personality (O Proactivity)mentioning
confidence: 99%
“…A poor P-E fit can lead to decreased job satisfaction, well-being, motivation, and commitment and increased turnover (Kristof-Brown et al, 2005). Implementing remote and smart working, for instance, can lead to increased feelings of isolation and disconnection from the organization and can negatively impact employees' well-being and motivation (Liang et al, 2022;Liao et al, 2021). Additionally, job insecurity and role ambiguity can lead to increased stress and anxiety among employees, negatively impacting their well-being and productivity (Sverke et al, 2002;Van der Heijden et al, 2004).…”
Section: Introductionmentioning
confidence: 99%